I have the next problem:
Suppose that a function $g$ satisfies that $-1\leq g(x) \leq 1$ for all $x\geq 0$.
Calculate $\lim_{x\to\infty}\dfrac{x+g(2x)}{g(3x)+4x}$

So: $$\lim_{x\to\infty}\dfrac{x+g(2x)}{g(3x)+4x}=\lim_{x\to\infty}\dfrac{\frac{x+g(2x)}{x}}{\frac{g(3x)+4x}{x}}=\lim_{x\to\infty}\dfrac{1+\frac{g(2x)}{x}}{\frac{g(3x)}{x}+4}$$ And because $-1\leq g(x) \leq 1$ then $\frac{g(2x)}{x}\to 0$ and $\frac{g(3x)}{x}\to 0$ as $x\to \infty$, therefore: $$\lim_{x\to\infty}\dfrac{1+\frac{g(2x)}{x}}{\frac{g(3x)}{x}+4}=\frac{1}{4}$$

But I don't know in which part I am using the squeeze/sandwich theorem, this is the second bullet of an exercise and the first bullet is just to enunciate the theorem.


It is straightforward that $$-1\le g(2x) \le 1 \implies -\frac{1}{x}\le \frac{g(2x)}{x} \le \frac{1}{x}\quad\text{ for }x>0.$$ Then, since $$\lim_{x\to \infty}{-\frac{1}{x}}=0=\lim_{x\to\infty}\frac{1}{x},$$ the squeeze theorem implies that $\displaystyle{\lim_{x\to \infty}\frac{g(2x)}{x}}$ exists and also it is equal to $0$.

Similarly, as a consequence of the squeeze theorem we get

$$\lim_{x\to \infty}\frac{g(3x)}{x}=0.$$


You can get the limit with a single application of the squeeze theorem.

For the numerator at $x>1$,

$$0<1-\frac{1}{x}\le 1+\frac{g(2x)}{x} \le 1+\frac{1}{x}$$

and for the denominator at $x>1$,

$$0<4-\frac{1}{x} \le \frac{g(3x)}{x}+4 \le 4+\frac{1}{x}$$

So for all $x>1$

$$\frac{1-\frac{1}{x}}{4+\frac{1}{x}} \le \frac{1+\frac{g(2x)}{x}}{\frac{g(3x)}{x}+4} \le \frac{1+\frac{1}{x}}{4-\frac{1}{x}}$$

and $\lim_{x\to\infty}{\frac{1-\frac{1}{x}}{4+\frac{1}{x}}}=\frac{1}{4}$ while $\lim_{x\to\infty}{\frac{1+\frac{1}{x}}{4-\frac{1}{x}}}=\frac{1}{4}$, so by the squeeze theorem



Get rid of $g(x)$ entirely. $-1\le g(x) \le 1$. So $x - 1 \le x + g(2x) \le x + 1$.

Likewise. $4x - 1 \le g(3x) + 4x \le 4x + 1$.

So $\dfrac{x - 1}{4x + 1} \le \dfrac{x + g(2x)}{g(3x) + 4x} \le \dfrac{x + 1}{4x - 1}$

So $1/4 = \lim\dfrac{x-1}{4x+1} \le \lim \text{wholeness} \le \lim \dfrac{x + 1}{4x - 1} = \dfrac14$.

Your method worked too. You used $\frac{-1}x \le \frac{g(2x)}x < \frac1x$ and $\frac{-1}x \le \frac{g(3x)}x < \frac1x$ for the squeeze theorem twice. It also works.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.